The politics of the prison and the prisoner: zoon politikon - Easton, Susan M. (Routledge, 2018)
chapter 1 The prisoner as a zoon politikon -- chapter 2 Political protest in prison -- chapter 3 The quest for citizenship in prison -- chapter 4 Losing citizenship in prison -- chapter 5 Discovering politics in prison -- chapter 6 The treatment of political prisoners -- chapter 7 Prisoners as a political problem.